Effect of Chronotype on Sleep Quality in a Laboratory Setting - HARFMANN, BRIANNA D. (Int J Exerc Sci, 2020)
Sleep is undoubtedly important for human health as insufficient sleep has been associated with a plethora of diseases. Adequate sleep assessment is critical in clinical and research settings, however current sleep assessment protocols fail to account for circadian rhythms, despite the fact that sleep is a well-recognized circadian process. Purpose: The purpose of this study was to determine if circadian parameters, such as chronotype, influence sleep quality in a sleep laboratory setting. Methods: In order to investigate this, twenty participants (10 men and 10 women) aged 18–31 years old had their sleep recorded by electroencephalography in a sleep lab. Participants also complete surveys which provided data on chronotype, social jet lag and subjective sleep quality. Participants were allowed to self-select sleep time for the study, and sleep discrepancy, defined as the difference between reported and experienced mid-sleep, was determined. Results: Interestingly, results indicated a significant correlation between self-reported sleep quality and social jet lag, with those who typically experience more social jet lag being more satisfied with their sleep during the study (r = 0.549, p = 0.012). In addition, when participants were separated into groups based on chronotype, sleep discrepancy and social jet lag, sizeable differences were noted for parameters such as sleep onset latency, number of awakenings, and percent of time spent in REM sleep. Conclusion: These results suggest circadian parameters serve as predictors of both subjective and objective sleep quality, and thus illuminates a necessity for these parameters to be taken into account in the assessment and research of sleep.